2022
DOI: 10.7717/peerj-cs.999
|View full text |Cite
|
Sign up to set email alerts
|

PPE detector: a YOLO-based architecture to detect personal protective equipment (PPE) for construction sites

Abstract: With numerous countermeasures, the number of deaths in the construction industry is still higher compared to other industries. Personal Protective Equipment (PPE) is constantly being improved to avoid these accidents, although workers intentionally or unintentionally forget to use such safety measures. It is challenging to manually run a safety check as the number of co-workers on a site can be large; however, it is a prime duty of the authority to provide maximum protection to the workers on the working site.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For instance, the Pictor-v3 [34] dataset emphasizes ensuring the proper wearing of safety helmets and vests by individuals. Lastly, there are combinations of the previous three categories, such as the Color Helmet and Vest (CHV) [35], CHVG [36], and FZU-PPE [37] datasets. Although these studies have achieved favorable experimental results, there are still some limitations.…”
Section: B Object Detection Methods For Ppementioning
confidence: 99%
“…For instance, the Pictor-v3 [34] dataset emphasizes ensuring the proper wearing of safety helmets and vests by individuals. Lastly, there are combinations of the previous three categories, such as the Color Helmet and Vest (CHV) [35], CHVG [36], and FZU-PPE [37] datasets. Although these studies have achieved favorable experimental results, there are still some limitations.…”
Section: B Object Detection Methods For Ppementioning
confidence: 99%
“…With the continuous progress of information technology and industrial technology, modern industrial production is developing in the direction of high speed, precision and intelligence, and data-driven [16,17] abnormal event diagnosis methods are gaining more and more attention and development, including the application of visual data for PPE detection. The vision-based methods can be divided into two categories: one is the traditional method of image processing combined with machine learning [5][6][7][18][19][20]; the other is using deep learning technology, e.g., object detection [9][10][11][12][21][22][23][24][25][26][27][28]. In the traditional approach, the region of interest (e.g., the head region or torso region) is usually first located using image processing techniques, and then image features [29][30][31] are extracted and machine learning methods are used to train a classifier to determine whether the region is a helmet or workwear.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the application in construction site, Hayat et al [ 34 ] used YOLO v5 to detect safety helmets on construction sites and showed excellent detection performance even in low light conditions. Ferdous et al [ 35 ] detected personal protective equipment on construction sites based on YOLO family’s anchor-free architecture, YOLOX, and found. YOLOX yields the highest mAP of 89.84% among the other three versions of the YOLOX.…”
Section: Related Workmentioning
confidence: 99%